(untitled) (Revista Brasileira de Contabilidade e Gestão, 2024)
Objective: This study sought to identify the 2030 Agenda practices adopted by a Credit Cooperative to promote sustainable development. Method(s): The study used a qualitative, exploratory-descriptive approach, the informatiom was collected through bibliographical and documentary research. The information collected was analyzed through content analysis, using Iramuteq software to process the information. Results: The research identified that the cooperative has three strategic drivers that are associated with promoting responsible solutions to cooperative members, contribute to local development and strengthen the cooperative’s business model in a sustainable way (relationship and cooperativism). It was also found that the financial institution has implemented a set of 15 sustainable development goals (SDG), in the services it provides to its members. Contributions: The results show that the cooperative has implemented a set of actions aimed at promoting sustainable development. However, it is suggested that the credit union needs to invest strategically and over the long term in projects aimed at the regions and municipalities where it operates, in order to achieve all the SDGs.